Disrupting the Archives and Loosening the Evangeline Knot: Finding an Undercurrent in Antoine-J. Léger’s Elle et lui and Une fleur d’Acadie - Thomas, Leanna (Acadiensis, 2022)
For marginalized francophone communities who left little written record in the colonial archives, 20th-century literature confronts absences and silences resulting from imperial archival dominance and popular narratives. This article mobilizes Acadian author Antoine-J. Léger’s novels Elle et lui : tragique idylle du peuple acadien (1940) and Une fleur d’Acadie : un épisode du grand dérangement (1946) to consider how Acadian writers began challenging the stability of archival records and subverting the dominance of the version of events imagined by Henry Wadsworth Longfellow in his poem Evangeline: A Tale of Acadie (1847).